(untitled) (Bangladesh Journal of Neuroscience, 2013)
Background: Epidemiologic studies have reported that microalbuminuria is a risk factor for stroke in men and a limited case control study found that the highest quintile of microalbuminuria values was associated with 13 fold increased risk for stroke. The goal of this study was designed to determine its relationship to risk factors for ischemic stroke. Materials and Methods: It was a prospective observational study conducted in the Department of Neurology, Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh. Fifty consecutive patients with ischemic stroke were enrolled in this study, with at least two risk factors that fulfilled the inclusion criteria and were confirmed by CT or MRI of brain. Equal number of controls of same age group without stroke who had at least two risk factors was compared with the case group. The patients were assessed clinically with structured questionnaire including blood pressure, height and weight, and monitoring blood glucose and microalbuminuria. Results: Microalbuminuria was found 58.0% in patients with ischemic stroke. Patients who had diabetes mellitus will have 13.86 times the risk for developing of microalbuminuria (p<0.05). Patients who had hypertension will have 4.19 times the risk of developing microalbuminuria (p<0.05) and BMI (e”23 kg/m2) will have 4.24 times the risk of developing microalbuminuria (p<0.05). Whereas TIA, IHD, dyslipidemia, smoking and positive family history were not significantly (P>0.05) associated with microalbuminuria in patients with ischemic stroke. Conclusion: The findings of this study show that diabetes is the factor most closely associated with microalbuminuria followed by HTN and BMI >23 kg/ m2 with statistically significance in patients with ischemic stroke. Bangladesh Journal of Neuroscience 2013; Vol. 29 (1) : 43-53